Experimental and Modeling Study of Soil Water Retention Curves of Compacted Bentonite considering Salt Solution Effects - Yong He; Ke-neng Zhang; Dong-yu Wu (Geofluids)
Due to its low hydraulic conductivity, high swelling capacity, and good adsorption properties, the Gaomiaozi (GMZ) bentonite has been selected as potential buffer/backfill materials for construction of engineered barriers in the deep geological repository for disposal of high-level nuclear waste (HLW) in China. Investigation of salt solution effects on the water retention properties of compacted bentonite is of great importance in the context of geological disposal of HLW based on the multibarrier concept. In this study, amended specimens were obtained through a spray of different concentrations of salt solutions to reach target salt contents, respectively. With employment of the vapor phase technique for suction control, water retention tests were conducted on densely compacted GMZ bentonite (1.7 Mg/m3) with different salt contents under confined conditions. Corresponding soil water retention curves (SWRCs) were obtained. Analysis indicates that, for a given suction, the measured water content of GMZ bentonite specimen increases as the salt content (or pore fluid concentration) increases. The influencing rate depends on suction. For lower suctions (lower than 38 MPa), the water retention capacity increases as the salt content increases, while for higher suctions (higher than 38 MPa), the influence can be negligible. Based on the Fredlund and Xing (1994) equation, a soil water retention model was proposed for simulation of the SWRCs of compacted GMZ bentonite with consideration of pore fluid chemistry. Parameters were analyzed and determined with consideration of influences of the pore fluid concentration. Verification indicates that the SWRCs simulated by the proposed model are well agreed with the measured ones.